Research on the Digital Earth Based on OpenGL - Li, De Jun; Quan, Ji Cheng; Wang, Hong Wei; Xie, Jun (Applied Mechanics and Materials, 2013)
OpenGL provides a good development platform for Digital Earth. With the development of three-dimensional computer visualization technology, the significant features of OpenGL will become more compatible with the trend of 3D GIS development. Through OpenGL, software technology and relative theories, especially with the progress of in-depth study of the Digital Earth, the goal building the three-dimensional digital globe has become possible, therefore, we can implement a three-dimensional methods on the initial development of Digital Earth by the visual programming environment of Visual C++ 6.0.